The Impact of Positive Feedback-Based Training on the Self-Confidence of Young Male and Female Athletes Flying Wheel Basketball Club (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
Confidence is an important psychological factor that affects athletes' performance, especially in adolescence. This study aims to determine the impact of positive feedback-based training on the confidence of adolescent basketball male and female athletes. The study used a pseudo-experimental method with a pretest-posttest control group design and involved 40 athletes, consisting of 12 experimental boys, 12 control boys, 8 experimental girls, and 8 control girls. For 8 weeks, the experimental group received training with a positive feedback approach, while the control group underwent regular training. Data were analyzed using paired t-test and independent t-test. The results showed a significant increase in the confidence of both the male (t = -66.77; p = 0.000) and female (t = -108.45; p = 0.000). The control group also improved, but to a much lesser extent. Posttest comparisons between groups showed significant differences between experimental and control sons (t = 12.59; p = 0.000) and between experimental and control daughters (t = 21.25; p = 0.000). These findings conclude that positive feedback is effective in boosting the confidence of adolescent athletes, and is recommended to be implemented in young age sports coaching programs.